Investigation of the barium enema x-ray examination as a significant contributor to the genetically-significant dose from diagnostic radiology - Engel-Hills, Penelope Claire (Division of Medical Physics, 2018)
The results of a study conducted by Maree (1995) indicated that the genetically-significant dose (GSD) for the white, female population in South Africa was considerably higher than the GSD for females in Great Britain, France and the United States of America. Further to this finding, Maree's study demonstrated that the barium enema x-ray examination was the major contributor to the GSD for this population group. A study of barium enema examinations was embarked on in order to explain the findings of Maree. The study was designed to include dose-area product measurements on patients having the barium enema procedure. In addition patient data and technique factors were recorded. The x-ray equipment used for the investigation was one digital and two non-digital fluoroscopic systems in the Western Cape. The digital unit utilised an overhead tube as did one of the conventional units. The other unit had an undercouch fluoroscopic tube and an overhead tube used for the standard radiography views. Comparison of the dose-area product measurements demonstrated that the unit having an undercouch tube had a mean dose-area product of 99.69 Gy cm² which culminates in a higher dose to the patient than the equipment utilising an overhead tube. The mean dose-area product of the two units with an overhead tube was 56.57 Gy cm² and 51.94 Gy cm² respectively. Free Air Exposure tables based on "RADCOMP Entrance Skin Exposure Software Program" (Nuclear Associates and Zamenhof, 1990) were used together with average technique factors to calculate skin entrance doses. These skin entrance doses were used to calculate gonad doses with the aid of a computer program from the Food and Drug Administration in the USA (Peterson and Rosenstein, 1989). The results were compared with the results of the barium enema component of the research conducted by Maree. The comparison indicated an average gonad dose for males of 242 μGy x 10⁻¹ (present study) compared to 485 μGy x 10⁻¹ (Maree) and an average gonad dose for females of 11185 μGy x 10⁻¹ (present study) compared to 16111 μGy x 10⁻¹ (Maree). Air-kerma at skin entrance was calculated using dose-area product measurements, recorded during the present study, for individual exposures and screening. These values were used to calculate the gonad dose. A discrepancy was demonstrated between the calculation of gonad dose from calculated as opposed measured skin entrance dose. The average gonad dose calculated by Maree is 16111 μGy x 10⁻¹ and the average gonad dose calculated for the present study using the measured skin entrance dose is 4236 μGy x 10⁻¹. This seems to explain the larger GSD estimated by Maree for the white female patients. A national protocol for measuring patient doses from x-ray examinations is proposed for South Africa.